Study Of Soil Erodibility Using The Erickson Method In The Downstream Of The Kombot Das, Pinolosian District, Bolaang Mongondow Selatan Regency - Tindage, Jorly Richarzon; Titah, Tilda; Kamagi, Yani Ezrah Bartolomeus (Jurnal Agroekoteknologi Terapan, 2024)
Watershed is a plain area bounded by hills or mountains that serves to store, accommodate, and drain water from upstream to downstream of the river. Watersheds (DAS) are part of the unity of resources where humans actively use them. In this study, the aspect studied was the condition of the soil texture which aims to determine the erodibility (K) of the soil around the Kombot watershed. This study used survey methods and laboratory analysis to obtain data on soil texture and erodibility (K).The results showed that: 1) The soil erodibility value was very high in the soil sample (1) with a K value of 0.60 at a slope of 0-400 with land use namely moor while soil texture class was dusty clay, 2) The soil erodibility value of low value is found in the soil sample (13) with a K value of 0.17 on slopes 9-140 with plantation land use while the soil texture class is sandy loam, 3) soil texture is a factor that affects the value of soil erodibility (K), because soil texture has sensitivity to erosion. Key words: Kombot watershed, soil erodibility, soil texture Abstrak Daerah Aliran Sungai (DAS) merupakan suatu wilayah dataran yang dibatasi oleh perbukitan atau pegunungan yang berfungsi sebagai tempat menampung, menampung, dan mengalirkan air dari hulu ke hilir sungai. Daerah Aliran Sungai (DAS) merupakan bagian dari kesatuan sumber daya yang dimanfaatkan secara aktif oleh manusia. Dalam penelitian ini aspek yang diteliti adalah kondisi tekstur tanah yang bertujuan untuk mengetahui erodibilitas (K) tanah di sekitar DAS Kombot. Penelitian ini menggunakan metode survei dan analisis laboratorium untuk memperoleh data tekstur dan erodibilitas tanah (K). Hasil penelitian menunjukkan bahwa: 1) Nilai erodibilitas tanah pada sampel tanah sangat tinggi (1) dengan nilai K 0,60 pada kemiringan 0-400 dengan penggunaan lahan yaitu tegalan sedangkan kelas tekstur tanah lempung berdebu, 2) Nilai erodibilitas tanah yang bernilai rendah terdapat pada contoh tanah (13) dengan nilai K sebesar 0,17 pada lereng 9-140 dengan penggunaan lahan perkebunan sedangkan kelas tekstur tanahnya adalah lempung berpasir, 3) tekstur tanah merupakan faktor yang mempengaruhi nilai erodibilitas tanah (K), karena tekstur tanah mempunyai kepekaan terhadap erosi. Kata kunci: DAS Kombot, Erodibilitas Tanah, Tekstur Tanah